73.4k views
23 votes
I neeeeddddd helllppppp I can’t sleeeeppp unlllleesss I dooo thisss

I neeeeddddd helllppppp I can’t sleeeeppp unlllleesss I dooo thisss-example-1
User Ohiovr
by
4.9k points

2 Answers

13 votes
No idea what the second one is but this is the first one Y=-2/3 x+66.66666666
User Eric Dand
by
6.1k points
2 votes

Explanation:

For no.4

m= -2/3

x=-60

y=10

now

y=mx+b

or,

10=-2x/3+b

or, 30=-2(-60)+3b

or, 30 = 120+3b

or,

3b = -90

so, b = -30

now

y=mx+b

or, y = -2x/3-30

for no.4 the equation would be

y = -2x/3 - 30

User Tinyfiledialogs
by
5.3k points